The late Americans - Taylor, Brandon (Brandon L. G.) (New York : Riverhead Books, 2023)
"In the shared and private spaces of Iowa City, a social circle of lovers and friends navigate tangled webs of connection as they try to figure out what they want, and who they are"--
"Author of Real Life, finalist for the Booker Prize"--Dust jacket.
Keywords: Novels